فقہی موضوعات سے متعلقہ آثارِ صحابہ کی جمع و تألیف (محققین کی خدمات کا تعارف وتجزیہ): The Compilation of the Athar of the Sahabah Relating to jurisprudential matters: An Introductory and Analytical Study of Scholarly Contributions (Al-Aasar, 2025)
Athaar e Sahaba are extremely effective in understanding religious rulings. Shar'ee rulings' original sources are Quran and Sunnah, but athaar e Sahaba help determine Quran and Sunnah's meanings. Many disputes regarding purification issues can be resolved in light of the athaar e Sahaba. The abundant existence of athaar e Sahaba regarding general prayer issues indicates their significance. n trade and transaction issues, jurist athaar e Sahaba opinions help solve modern economic problems. Researchers have made excellent contributions on athaar e Sahaba topic-wise in jurisprudence as well. Several important compilations and encyclopedias have also been arranged on athaar e Sahaba.